Fieldwork of the Canadian Institute in Greece in 2019–2020 - Perreault, Jacques Y. (Mouseion, 2024)
The archaeological fieldwork conducted in Greece in 2019 and 2020 under the aegis of the Canadian Institute in Greece is reported here, based on the presentation given by the director at the Institute's annual Open Meeting in 2021.

Rapport sur les travaux de l'école française en Grèce en 1987 - Pariente, Anne; Aupert, Pierre; Moretti, Jean-Charles; Pentazos, Evangelos; Déroche, Vincent; Queyrel, François; Sève, Michel; Péristeni, Katérina; Treuil, René; Perreault, Jacques-Y; Empereur, Jean-Yves; Simossi, Angeliki; et al. (Bulletin de Correspondance Hellénique, 1988)

Argilos, 25 années de recherches : organisation de la ville et de la campagne dans les colonies du nord de l’Égée, VIIIe - IIIe siècles av. n. è. : actes du colloque de Thessalonique, 25-27 mai 2017 - Bonias, Zisis; Perreault, Jacques Y. (The Canadian Institute in Greece, 2021)
Argilos. 3, Άργιλος, 25 χρόνια έρευνας : οργάνωση πόλης και χώρας στις αποικίες του βορείου Αιγαίου, 8ος-3ος αι. π. Χ.: πρακτικά του συνεδρίου της Θεσσαλονίκης, 25-27 Μαΐου 2017 / επιμ. Ζήση Μπόνια [Zisis Bonia] και Jacques Y. Perreault ; με τη συνεργασία Saskia Deluy και Laure Sarah Éthier

Το αγγειοπλαστείο στο Φαρί της Θάσου - Perreault, Jacques; Blondé, Francine; Peristeri, Katerina (Κεραμικά εργαστήρια στο Βορειοανατολικό Αιγαίο (8ος-αρχές 5ου αι. π.Χ.): ημερίδα ΑΜΘ 2010, 2013)
Overview of the architectural remains of a Late Archaic pottery workshop (late-6th/early-5th cent. B.C.) unearthed at Fari, Thasos, during excavations conducted between 1985 and 1989 by the Ephorate of Antiquities of Kavala and the French School at Athens.

Έλληνες και Θράκες στην παραλία ζώνη και την ενδοχώρα της Θράκης στα χρόνια πριν και μετά τον μαγάλο αποικισμό - Bonias, Zissis; Perreault, Jacques Y. (2009)

L' habitat d'Argilos: les céramiques archaïques, un aperçu - Perreault, Jacques Y.; Bonias, Zisis I. (Les clients de la céramique grecque: actes du colloque de l'Académie des inscriptions et belles-lettres, Paris, 30-31 janvier 2004, 2006)
Description de la céramique par phases chronologiques entre 650 et 500 av. J.-C.

Travaux récents à la basilique de Ras el Bassit: vestiges des IIIe-IVe s. - Beaudry, Nicolas; Perreault, Jacques Y. (Annales Archéologiques Arabes Syriennes, 2002)
Les fouilles reprises depuis 2000 par l'Université de Montréal ont dégagé des vestiges des 3e-6e s. Une chapelle médiévale succède ensuite à la basilique byzantine. À noter une plaque de marbre inscrite en grec et inédite, retaillée et remployée en placage

Les ateliers de potiers dans le monde grec aux époques géométrique, archaïque et classique: actes de la table ronde organisée à l'École française d'Athènes (2 et 3 octobre 1987) - Blondé, Francine; Perreault, Jacques Y. (De Boccard, 1992)

Les débuts de la présence effective de Grecs sur la côte syro-palestinienne à l'âge du fer - Perreault, Jacques Y. (O Ellinismos stin Anatoli: praktika a'diethnous archaiologikou sunedriou, Delphoi 6-9 Noemvriou 1986 = International meeting of history and archaeology, Delphi 6-9 November 1986, 1991)
Analyse des importations grecques, notamment de leur répartition géographique et quantitative.

Céramique et échanges. Les importations attiques au Proche-Orient du VIᵉ au milieu du Vᵉ siècle avant J.C. Les données archéologiques - Perreault, Jacques Y. (Bulletin de Correspondance Hellénique, 1986)
La céramique attique est, dès son apparition au Proche-Orient, un produit de demi-luxe qui fait l'objet d'échanges commerciaux réguliers. Ce matériel montre notamment l'originalité et la relative indépendance de chaque cité dans ses relations avec les Grecs. Il permet aussi de déterminer des périodes d'activité intense suivies de brusques ruptures. La période étudiée connaît de profonds changements dans l'organisation du commerce tant à l'ouest qu'à l'est.

The Wall Paintings of the Panagia Olympiotissa at Elasson in Northern Thessaly, 2 Volumes - Constantinides, Efthalia C (Canadian Archaeological Institute at Athens, 1992)
Keywords: Art/Architecture

Les emporia grecs du Levant: mythe ou réalité? - Perreault, Jean Y. (L'Emporion, 1993)

Production et distribution à l’époque archaïque: le cas d’un atelier de potier de Thasos - Perreault, Jacques Y. (The Complex Past of Pottery, 1999)
Section: The Complex Past of Pottery
Keywords: Archaeology; Art & Architecture; Classical Studies; _CL

Άργιλος, Ανασκαφή 1998-1999 - Bonias, Z.; Perreault, J. (To Archaiologiko Ergo sti Makedonia kai Thraki, 2000)

Argilos: A Greek Colony in Thracian Territory - Perreault, J.; Bonias, Z. (The AAIA Bulletin, 2006)

Rapport sur la mission archéologique 2007 à Ras el Bassit - Beaudry, Nicolas; Perreault, Jacques Y.; Mills, Philip J. E. (Chronique Archéologique en Syrie. Special Issue Documenting the Annual Excavation Reports Concerning the Archaeological Activities in Syria. Excavation Reports of 2007, 2008)
Keywords: _CL

3. Argilos aux VIIe - VIe siècles - Perreault, Jacques-Yves; Bonias, Zisis (Grecs et indigènes de la Catalogne à la mer Noire : Actes des rencontres du programme européen Ramses2 (2006-2008), 2010)
This article deals with the Greek colonization of ancient Argilos which took place towards the middle of the 7th century B.C., and addresses the question of cohabitation between the Greek colonists and the native Thracian population. A study of the archaeological remains, the literary sources and the development of Greek penetration in the lower region of the Strymon river tends to show that Greeks and Thracians did live together in Argilos, but also in several other sites of this region.
Code: Grecs et indigènes de la Catalogne à la mer Noire : Actes des rencontres du programme européen Ramses2 (2006-2008)
Keywords: Thraces; colonisation grecque

The Fieldwork of the Canadian Institute in Greece, 2010 - Rupp, David W.; Bonias, Zisis; Perreault, Jacques Y.; Karapanou, Sophia; Haagsma, Margriet J.; Begg, D. J. Ian; Nelson, Michael C.; Aravantinos, Vassilis; Burke, Brendan; Burns, Bryan; Tankosic, Zarko; Keller, Donald R. (Mouseion: Journal of the Classical Association of Canada, 2012)
The archaeological fieldwork conducted in Greece in 2010 under of aegis of the Canadian Institute in Greece is summarized on the basis of a presentation given by the director at the institute’s annual Open Meeting in Athens, in May 2011. These research activities included excavations (Argilos and Kastro Kallithea), a pedestrian survey (Karpathos), and study seasons (Eastern Boeotia and Southern Euboea). , Les travaux archéologiques menés en Grèce en 2010 sous l’égide de l’Institut canadien en Grèce sont passés en revue dans le cadre d’une présentation donnée par le directeur lors de l’Assemblée publique annuelle, tenue à Athènes en mai 2011. Ces recherches comptaient des fouilles (Argilos et Kastro Kallithéa), une prospection (Karpathos) et des campagnes d’étude (Boétie orientale et Eubée sud).

The Fieldwork of the Canadian Institute in Greece, 2011 - Rupp, David W.; Aravantinos, Vassilis; Burke, Brendan; Burns, Bryan; Begg, Ian; Nelson, Michael; Brenningmeyer, Todd; Kelly, Amanda; Bonias, Zisis; Perreault, Jacques; Karapanou, Sophia; Haagsma, Margriet (Mouseion: Journal of the Classical Association of Canada, 2012)
The archaeological fieldwork conducted in Greece in 2011 under the aegis of the Canadian Institute in Greece (CIG) is summarized based on the presentation given by the director at the institute’s annual Open Meeting in Athens in May 2012. , Les travaux archéologiques menés en Grèce en 2011 sous l’égide de l’Institut canadien en Grèce sont présenté sur la base d’une allocution donnée par le directeur lors de l’assemblée publique annuelle à Athènes en mai 2012.

L'atelier de potier archïque de Phari (Thasos) : la production de tuiles - Perreault, Jacques Y. (Hesperia: The Journal of the American School of Classical Studies at Athens, 1990)
The roof tiles and covering joints of Laconian type discovered in an ancient workshop at Thasos between 1985 and 1988 can most likely be dated between the last quarter of the 6th cent. B.C. and the first quarter of the 5th cent. The presence of vase fragments at the site raises the possibility that both tiles and vases were produced in the same shop – an apparent rarity for this period.

Ancient Mines and Quarries: A Trans-Atlantic Perspective - Barber, Martyn; Brumbach, Hetty Jo; Ellis, Christopher J.; Desrosiers, Pierre M.; Gauthier, Gilles; Julig, Patrick J.; Llach, Xavier Mangado; Moreau, Jean-François; Perreault, Jacques Y.; Revez, Jean; Ritchie, Duncan; Varndell, Gillian (Oxbow Books, 2010)
Fourteen papers explore a range of issues relating to prehistoric extraction sites, including ethnography, geochemical signatures, the application of neutron activation analysis, exploitation of erratics, excavation, survey and conservation. Topics include quernstone extraction, use of hammers, stages of extraction, geographical and social contexts, changing social regimes, the ritualised nature of journeys to quarry sites, study of petrofabrics, and the effects of joint and cleavage on quarrying practice. Two contributions are in French with extended summaries in English.

After Zagora — Andrian Colonization in the Northern Aegean: The Case of Argilos - Perreault, Jacques Y.; Bonias, Zisis (Mediterranean Archaeology: The Australian and New Zealand Journal for the Archaeology of the Mediterranean World, 2012)
For the last twenty years, a team of Greek and Canadian archaeologists have been excavating Argilos, the earliest known Greek colony in the area of the mouth of the Strymon river. An overview of research on what was one of the four colonies founded by Andrians after the abandonment of Zagora allows discussion of questions related to the origin of the settlers, the choice of location, the foundation date, and the reasons for the settlement. First occupied by Thracians, Argilos was settled by Greeks no later than the mid-7th cent. B. C. Some of these Greeks came from Andros ; however, one should not eliminate the possibility that Argilos may have been a joint venture between Andrians and Chalcidians. Cohabitation between Greeks and Thracians lasted until the mid-6th cent., when it is believed a wave of immigrants arrived, some of whom were from east Greece. Argilos remained affluent until the foundation of Amphipolis in 437, after which it suffered decline. Its capture by Philip II in 357 and the deportation of its inhabitants to Amphipolis put an end to its existence.

The Fieldwork of the Canadian Institute in Greece, 2012 - Rupp, David W.; Charami, Alexandra; Burke, Brendan; Burns, Bryan; Bonias, Zizis; Perreault, Jacques Y.; Karapanou, Sophia; Haagsma, Margriet J. (Mouseion: Journal of the Classical Association of Canada, 2016)

Fieldwork of the Canadian Institute in Greece in 2013 - Rupp, David W.; Bonias, Zizis; Burke, Brendan; Burns, Bryan; Carter, Tristan; Charami, Alexandra; Haagsma, Margriet J.; Karapanou, Sophia; Perreault, Jacques Y. (Mouseion: Journal of the Classical Association of Canada, 2016)

Isotopic evidence for animal management strategies at Archaic and Classical period Argilos, Greece - Alagich, Rudolph; Gkotsinas, Angelos; Perreault, Jacques Y.; Bonias, Zisis; Smith, Colin (Journal of Archaeological Science: Reports, 2022)
This paper utilizes the stable carbon and nitrogen isotopic composition of bulk animal bone collagen to better understand animal management practices in Archaic and Classical period Argilos in northern Greece. The results from Argilos are compared with data from other sites in northern Greece to provide new insights into herd management in the region over time. Our results reveal some changes in cattle and pig diets at Argilos between the Archaic and Classical periods. Throughout both periods cattle and caprines exhibit evidence of having consumed C4 vegetation, likely obtained from the nearby salt marshes in the Strymon river delta. This dietary regime is similar to that observed at other north Aegean sites dating back to the Neolithic, suggesting that the long tradition of animal herding in the marshes was an environmentally specific practice in the region.
Keywords: Agriculture; Argilos; Classical period; Greece; Stable isotopes

Fieldwork of the Canadian Institute in Greece in 2014 - Rupp, David W.; Carter, Tristan; Charami, Alexandra; Burke, Brendan; Burns, Bryan; Bonias, Zizis; Perreault, Jacques Y.; Nakassis, Dimitri; Gallimore, Scott; James, Sarah; Karapanou, Sophia; Haagsma, Margriet J. (Mouseion: Journal of the Classical Association of Canada, 2017)
The archaeological fieldwork conducted in Greece in 2014 under the aegis of the Canadian Institute in Greece is summarized here based on the presentation given by the Director at the Institute’s annual Open Meeting in Athens in May 2015.

Fieldwork of the Canadian Institute in Greece in 2015 - Rupp, David W.; Bonias, Zizis; Perreault, Jacques Y.; Charami, Alexandra; Burke, Brendan; Burns, Bryan; Carter, Tristan; Athanasoulis, Dimitris; Nakassis, Dimitri; Gallimore, Scott; James, Sarah; Karapanou, Sophia; et al. (Mouseion: Journal of the Classical Association of Canada, 2018)
The archaeological fieldwork conducted in Greece in 2015 under the aegis of the Canadian Institute in Greece (CIG) is summarized based on the presentation given by the director at the institute's annual Open Meeting in Athens in May 2016.

Fieldwork of the Canadian Institute in Greece in 2016 - Rupp, David W.; Bonias, Zizis; Perreault, Jacques Y.; Charami, Alexandra; Burke, Brendan; Burns, Bryan; Carter, Tristan; Athanasoulis, Dimitris; Nakassis, Dimitri; Gallimore, Scott; James, Sarah; Karapanou, Sophia; et al. (Mouseion: Journal of the Classical Association of Canada, 2019)
The archaeological fieldwork conducted in Greece in 2016 under the aegis of the Canadian Institute in Greece is summarized here based on the presentation given by the Director at the Institute's annual Open Meeting in Athens, in May, 2017.

Fieldwork of the Canadian Institute in Greece in 2017 - Rupp, David W.; Carter, Tristan; Athanasoulis, Dimitris; Charami, Alexandra; Burke, Brendan; Burns, Bryan; Papadimitriou, Alcestis; Perreault, Jacques Y.; al, et (Mouseion: Journal of the Classical Association of Canada, 2020)
Number: 2

Fieldwork of the Canadian Institute in Greece in 2018 - Burke, Brendan; Athanasoulis, Dimitris; Bonias, Zisis; Burns, Bryan; Carter, Tristan; Charami, Alexandra; Gallimore, Scott; Haagsma, Margriet J.; James, Sarah; Karapanou, Sophia; Nakassis, Dimitri; Papadimitriou, Alcestis; et al. (Mouseion: Journal of the Classical Association of Canada, 2021)
The archaeological fieldwork conducted in Greece in 2018 under the aegis of the Canadian Institute in Greece (CIG) is summarized based on the presentation given by the director at the Institute’s annual Open Meeting in Athens in May 2019.
Number: 2

Argilos: the booming economy of a silent city - Perreault, Jacques Y.; Bonias, Zisis (Making cities: Economies of production and urbanization in Mediterranean Europe, 1000–500 BC, 2021)